Functions of Parents Homeschooling Their Children: The Case of Lithuania - Naidaitė, Edita; Stasiūnaitienė, Eglė (Acta Paedagogica Vilnensia, 2023)
The article presents the most illustrative results of a broader empirical study carried out in Lithuania in 2021–2022. The aim is to answer the question of what the functions of parents are and how the child’s education is organised in the case of homeschooling. The research data were collected using a semi-structured interview method and were processed using content analysis. The data were analysed under the topic “Functions of parents homeschooling their children”. The topic combines the following seven sub-topics: planning and organising the educational process, selecting/developing educational content, designing learning environments, ensuring a safe learning environment, recording learning achievements, assessing learning achievements, and ensuring socialisation. The research involved ten informants (five parents homeschooling their children and five heads of educational institutions) selected by criterion sampling. To summarise the results of the empirical research, it should be highlighted that when parents choose to homeschool their children, they essentially take over the main function of educational institutions and become responsible for the organisation of the entire educational process. The child is involved in the planning of the educational process; the individual needs of the child are better taken into account, and the child’s autonomy is encouraged. The curriculum and schedule are flexible, based on the child’s acquired knowledge, competences, and skills rather than on the number of lessons. Educational environments are constantly changing and are usually chosen by the child. Parents who participated in the study have identified difficulties in analysing the documents of the education system and the lack of access to the electronic diary. The heads of educational institutions have expressed doubts about the pedagogical preparation of parents to homeschool their children and to ensure purposeful socialisation; however, the parents have noted that socialisation is sufficient and takes place according to the child’s individual needs. In the authors’ opinion, the research carried out raises topical issues for discussion and the initiation of new research in this area, with the aim of better understanding the context of the phenomenon of homeschooling.